The effect of financing using the principle of profit-loss sharing on profitability level of commercial Islamic bank registered in Bank Indonesia - Nurul Alfi Syahri; Dwipraptono Agus Harjito (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: This study aims to examine the effect of financing products with the principle of profit-loss sharing offered by Sharia Banks to the level of profitability of Sharia Banks. The financing product under profit sharing principle of Sharia Bank can be categorized into two types namely Mudharaba and Musharaka. The effect of Mudharaba and Musharaka on the profitability level of Sharia Banks is tested partially and simultaneously. In this study, the profitability level of Sharia Bank is measured by Return On Equity (ROE).Methodology: The sample of this research is the Sharia Bank registered in Bank Indonesia. The sample selection in this study used purposive sampling method and obtained6 samples for the study period of 2012-2016. This research uses Multiple Linear Regression analysis method to analyze the data.Findings: Results of this study indicate that financing products with profit-loss sharing principles represented by the proxy of Mudharaba and Musharaka have a significant effect on the profitability level of Sharia Banks for the period of 2012-2016. Mudharaba is partially significant and positive to the profitability level of Sharia Banks for the period of 2012-2016, Musharaka partially has a significant and negative effect on the profitability level of Sharia Banks for the period of 2012-2016, and Mudharaba and Musharaka simultaneously have a significant influence to the level of profitability of Sharia Banks for the period of 2012-2016.Originality: This study enriches the discussion of the effect of financing products with the principle of profit-loss sharing offered by Sharia Banks to the level of profitability of Sharia Bank. The effect of Mudharaba and Musharaka on the profitability level of Sharia Banks is tested to the profitability level of Sharia Banks